2003
DOI: 10.1074/jbc.m209719200
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and Molecular Modeling ofS-Adenosyl-l-methionine Binding Sites inN-Methyltransferase Domains of the Multifunctional Polypeptide Cyclosporin Synthetase

Abstract: We employed a highly specific photoaffinity labeling procedure, using 14 The modified sequence regions correspond to the motif II consensus sequence element, which is involved in directly complexing the adenine and ribose components of AdoMet. We conclude that the AdoMet binding to nonribosomal peptide synthetase N-methyltransferase domains obeys the consensus cofactor interactions seen among most structurally characterized low molecular weight AdoMet-dependent methyltransferases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 69 publications
(82 reference statements)
0
20
0
1
Order By: Relevance
“…The effect of the remaining amino acid residues in the SAM-binding site has not been verified by mutations. However, residues which form the SAM-binding site (Velkov & Lawen, 2003) were found to be replaced only in Microcystis strains producing desmethyl 7 -microcystin, and always with residues with different physicochemical properties (Fig. 3A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of the remaining amino acid residues in the SAM-binding site has not been verified by mutations. However, residues which form the SAM-binding site (Velkov & Lawen, 2003) were found to be replaced only in Microcystis strains producing desmethyl 7 -microcystin, and always with residues with different physicochemical properties (Fig. 3A).…”
Section: Discussionmentioning
confidence: 99%
“…The amino acid residues constituting the S-adenosylmethionine (SAM)-binding site of cyclosporin synthetase NMT domains (Velkov & Lawen, 2003) were identified in the deduced amino acid sequences of the NMT domains. The NMT domain sequence from Microcystis strain K-139 (AB019578), which exclusively produces [Dha 7 ]-MC, was also included in the NMT dataset.…”
Section: A Tooming-klunderud and Others 1888mentioning
confidence: 99%
“…Our group employed a highly specific photoaffinity labeling procedure, using 14 C-labeled AdoMet to define the chemical structure of the AdoMet binding centers of CySyn. Stoichiometric photoaffinity labeling demonstrated that CySyn is photolabeled with AdoMet in a molar ratio of ~7:1 (AdoMet:CySyn [45]), which is in good agreement with the seven N-MTase domains identified in the CySyn cDNA sequence [22]. The specificity of photolabeling was demonstrated by competitive displacement with nonradioactive AdoMet and its inhibitory analogs S-adenosyl-l-ethionine, S-adenosyl-l-homocysteine, and sinefungin [44,46].…”
Section: N-methylationmentioning
confidence: 64%
“…Accordingly, the N-MTase domains of CySyn can be assigned as small molecule MTases. The presence of functional N-MTase activity in the CySyn polypeptide was first demonstrated by photoaffinity labeling with [methyl- 14 C] AdoMet and by the ability of the purified enzyme to transfer the sulfonium methyl group from [methyl- 14 C] AdoMet to CsA [18,45]. Most AdoMet-dependent MTases have a bilobial structure and are organized into an AdoMet binding domain, which provides cofactor binding contacts and catalytic residues, and a second domain mainly responsible for conferring substrate specificity [35][36][37].…”
Section: N-methylationmentioning
confidence: 99%
“…Generally, three kinds of motif contribute to the 12) Among them, motif I has been shown to be present in most methyltransferases. 13) At the C-terminal of AfsK, we found two SAM-binding motifs similar to conserved motif I (Fig. 2A).…”
Section: Resultsmentioning
confidence: 91%